A Lineage of Leakers?: The contingency of collective memory in coverage of contemporary leaking cases. (26th November 2018) - Thomas, Ryan J.; Perreault, Mildred F.
Abstract : This study draws on the theoretical framework of collective memory to ascertain the ways in which a story from journalism's past—Daniel Ellsberg and the Pentagon Papers—was brought to bear in coverage and commentary of a broadly analogous story in journalism's present—WikiLeaks, Chelsea (formerly Bradley) Manning, and Edward Snowden. The discourse was far from uniform, which we see as indicative of the contingencies of collective memory. We find four themes: (1) lack of consensus on whether Ellsberg, Manning, and Snowden constituted a lineage of leakers, as some journalists contended, or if there are distinctions to be drawn; (2) discussion about the contingencies of historical representation and awareness of the role of "victors" in shaping history; (3) celebrations of journalism and its storied history amid a backdrop of flux; and (4) discussion of changes in technology and how they impacted the methods of the leakers. Theoretical and methodological implications for the study of journalism and collective memory are discussed.